Water dynamics in plant production - Ehlers, Wilfried (CABI Pub., 2003)
This book contains 19 chapters providing the basic principles of water transport in the soil-plant-atmosphere continuum and demonstrating how they can be used in practical soil and crop management. Topics covered include the roles of water in plant and soil, interdependency of soil water and vegetation, properties and energy state of water, water storage and movement in soil, and uptake, balance and use of water by the plant/crops. Radiation interception and dry matter accumulation as well as the influence of nutrient supply on water use and establishment of yield and yield formation under inadequate water supply are considered. In addition, measurement of water stress in plants, effects of climatic change on yield, and future strategies for plant breeding are discussed. Finally, the control of soil water balance by soil management (e.g. conservation tillage), and of water use by crop management (e.g. rotations, choice of species/cultivars, sowing and fertilizer application), and irrigation systems are also discussed.